Hoàn thiện hoạt động quản trị rủi ro tín dụng tại Chi nhánh Ngân hàng Ngoại thương Hà Nội - Lại Thị Kim Cúc,Nguyễn Kim Anh
Hoàn thiện hoạt động quản trị rủi ro tín dụng tại Chi nhánh Ngân hàng Ngoại thương Hà Nội , 2007